Web-Based Altamart Store Sales System Design - Amara Yulia F.P; Imam Wahyudi; Marini Styawati; Tinuk Agustin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Altamart is a grocery store that serves buying and selling transactions for goods for daily needs. Altamart also provides various types of food and drinks such as snacks, bread, instant noodles, syrup, mineral water, and others. Altamart still uses manual tools for transactions in stores. Therefore, to develop technology, a Web-Based Application was designed to improve performance at the Altamart store. Simply using this application consumers can transact remotely, consumers can also find out the total price of goods to be purchased, consumers know the details of goods easily and billing records can be accessed via the internet and also consumers can choose various payment systems offered. In addition, consumers can also choose a home delivery service. So consumers can wait for the goods to be delivered to their destination without having to come to the store. However, it can only deliver within the surrounding area. From this research a WEB-Based Application was created for buying and selling transactions that can make it easier for buyers, also makes it easier for users (Grocery Stores), so that it can help users record incoming and outgoing goods or if you make points, the results obtained are based on trial results are as follows: (1) WEB-Based Application for ordering goods has been successfully created; (2) With the Goods Ordering Application, consumers can find out information on the stock of goods and prices of goods, for users it can make it easier to manage stock of goods; (3) Providing accurate and up-to-date stock information; (4) This application is for ordering goods in the store